Self-Esteem of Female Prisoners - Etty Eriyanti; Megah Andriany; Muhammad Muin (Faculty of Nursing, Universitas Jember, 2020)
Female prisoners are special communities that are vulnerable to a decline in self-esteem. The purpose of this study is to describe the self-esteem of female prisoners in Semarang female prisons. Researchers used descriptive designs in this study. The results showed that the most women prisoners' self-esteem were moderate self-esteem (81.0%), high self-esteem (16.5%), and low self-esteem (2.5%). Most female prisoners experience a decrease in self-esteem, so that various efforts are needed to improve the self-esteem of female prisoners, especially community-based nursing interventions.